Modal verbs in Indonesian and Malaysian English textbooks for secondary schools: A corpus-driven study - Ikmi Nur Oktavianti; Noor Raha Mohd Radzuan; Bambang Widi Pratolo; Surono Surono; Tri Rina Budiwati; Shifak Aisyah (Universitas Syiah Kuala, 2025)
Modality is a salient notion in language, manifested through modal verbs. However, modal verbs are complex grammatical units since they have multiple functions and meanings. Previous studies have shown mismatches between actual language use and its presentation in textbooks, including modal verb representation in both EFL and ESL contexts. This study explored the distributional frequencies of modal verbs in Indonesian EFL textbooks compared to those in Malaysian ESL textbooks. It compiled the textbook conversation corpora from secondary education levels in Indonesia and Malaysia: two Indonesian EFL textbooks (IET) and two Malaysian ESL textbooks (MET), which are nationally endorsed. The corpora comprised 4,548 tokens collected from the conversations in the textbooks. Data collection involved corpus queries focusing on nine core/central modal verbs: can, could, may, might, shall, should, will, would, and must. The results show that Indonesian and Malaysian textbooks shared the same most frequent modal verb distribution; however, other distributions differed. Besides, English modal verbs in Indonesian textbooks are more static with one-to-one correspondence, while Malaysian textbooks present more dynamic modal verb meanings. Notably, Indonesian EFL textbooks have complete modal meaning representation, which is absent in Malaysian textbooks. Interestingly, the modal verb distributions in both textbooks differ from those in a native corpus, representing actual English use. These results highlight the need for more careful consideration when designing and developing teaching materials, especially in ESL and EFL contexts.